Cuidado, pajarito! - Janovitz, Marilyn; Alejandro, Alis. (New York : Ediciones Norte-Sur, 1997)
A snail starts a chain reaction involving many animals when it slips off a branch and hits a bird.
First published in English under title: Look Out, Bird!
Accelerated Reader
Keywords: Snails -- Juvenile fiction; Birds -- Juvenile fiction; Animals -- Juvenile fiction; Caracoles -- Novela juvenil; Aves -- Novela juvenil; Animales -- Novela juvenil